Effects of Imago Relationship Therapy on Spousal’s emotional instability married teachers in Kwara State, Nigeria - Habibat Bolanle Abdulkareem; Kamil Adekola Lasis (Inovasi Kurikulum, 2024)
The study delved into the impact of Imago Relationship Therapy on spousal emotional instability using Ancova for analysis. The study adopted a pretest-posttest, control group quasi-experimental design with a 2x2x3 factorial matrix. Two primary schools were randomly selected, and convenient sampling techniques were used to select 60 participants in the selected schools 30 participants were meant for the treatment group and 30 for the control group. Results indicated significant effects: The therapy showcased a substantial reduction in emotional instability (F = 594.276, p smaller than 0.001), with the overall model explaining 95.2 percent of the variance. Gender (F = 1.859, p = 0.001) and self-esteem (F = 3.755, p = 0.001). An interaction between gender and self-esteem, as well as the three-way interaction (GROUP Gender Self-esteem), were statistically significant, emphasizing the interconnectedness of these factors in understanding emotional instability. It was recommended that the school counselors should assist teachers in overcoming their mindfulness. AbstrakStudi ini menyelidiki dampak Terapi Hubungan Imago terhadap ketidakstabilan emosi pasangan menggunakan Ancova untuk analisis. Penelitian ini menggunakan desain eksperimen semu kelompok kontrol pretest-posttest dengan matriks faktorial 2x2x3. Dua sekolah dasar dipilih secara acak dan teknik convenience sampling digunakan untuk memilih 60 peserta. Di sekolah yang dipilih, sampel penelitian dibagi menjadi 30 peserta untuk kelompok perlakuan dan 30 untuk kelompok kontrol. Hasil penelitian ini menunjukkan efek yang signifikan: terapi menunjukkan penurunan substansial dalam ketidakstabilan emosi (F = 594,276, p lebih kecil dari 0,001), dengan model keseluruhan menjelaskan 95,2 persen varians. Gender (F = 1.859, p = 0.001) dan harga diri (F = 3.755, p = 0.001). Interaksi antara gender dan harga diri, serta interaksi tiga arah (GROUP Gender Self-harga diri), adalah signifikan secara statistik, menekankan keterkaitan faktor-faktor ini dalam memahami ketidakstabilan emosi. Disarankan agar konselor sekolah membantu guru dalam mengatasi mindfulness mereka.Kata Kunci: ketidakstabilan emosional; gender; guru yang sudah menikah; harga diri